How effective is the obesity treatment on improving oxidative stress? Is there any difference between drugs? - Lezan Keskin; İbrahim Şahin; Dilek Gogas Yavuz; Meral Yüksel; Mehmet Çağatay Taşkapan (Northwestern Medical Journal, 2022)
Aim: Obesity shortens the life period and decreases its quality, causing several complications. Recently, oxidative stress produced by lipid peroxydation is considered a cardiovascular risk factor. In this study, we aimed to investigate the relationship between weight loss with lipid profile, insulin resistance, and lipid peroxidation products malondialdehyde (MDA, oxidant) and paraoxonase-1 (PON1, antioxidant) levels which is protective in atherosclerosis, and to evaluate alteration on oxidative stress.